Clinical evaluation of double-channel gastroscope for endoscopic retrograde cholangiopancreatography in patients with Billroth II gastrectomy - Wang, Sheng; Liu, Wen; Sun, Siyu; Wang, Guoxin; Liu, Xiang; Ge, Nan; Guo, Jintao (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Aim : To evaluate the use of a double-channel gastroscope in patients with Billroth II gastrectomy to perform endoscopic retrograde cholangiopancreatography (ERCP) and interventions. Material and methods: From January 2008 to December 2013, 18 patients with Billroth II gastrectomy were enrolled in this study. Endoscopic retrograde cholangiopancreatography was performed using a straight forward gastroscope with double working channel (4.2-mm diameter, 2.8-mm diameter). Results: The success rate of selective cannulation and accomplishment of planned procedures was 15 out of 18 patients (83.3%), and no serious complications were encountered. Conclusions : The double-channel gastroscope appears to be useful in performing endoscopic retrograde cholangiopancreatography in patients with Billroth II gastrectomy.